Heat Transfer in Boundary Layer Magneto-Micropolar Fluids with Temperature-Dependent Material Properties over a Stretching Sheet - Ephesus O. Fatunmbi; Samuel S. Okoya (Advances in Materials Science and Engineering)
The process of heat transfer in boundary layer magneto-micropolar fluid with temperature-dependent material properties past a flat stretching sheet in a porous medium is investigated in this study. Two distinct cases of boundary heating conditions are analyzed for the heat transfer in this work, viz., prescribed surface temperature (PST) and prescribed heat flux (PHF). With the aid of similarity conversion analysis, the formulated equations of the flow and heat transfer have been translated into a system of nonlinear ordinary differential equations. Subsequently, Runge–Kutta–Fehlberg integration scheme in company of shooting techniques employed to obtain numerical solutions to the reduced equations. The findings are graphically illustrated and discussed in view of the two cases of boundary heating, while the results for the physical quantities of engineering concern are tabulated for various controlling parameters. In the limiting situations, the results generated are compared favourably with the earlier reported data in the literature, while the numerical solutions demonstrate a reduction in the rate of heat transfer Nux⋆ and the viscous drag Cf⋆ for both PST and PHF conditions with growth in the magnitude of material parameter K.